Optimization of two- dimensional photonic crystal waveguides for TE and TM polarizations - Danaie, Mohammad; Attari, Amir Reza; Mirsalehi, Mir Mojtaba; Naseh, Sasan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In this paper, we optimize the geometries of some 2D photonic crystal waveguides to increase their single-mode bandwidths for TE and TM polarizations. Using the Plane Wave Expansion (PWE) method combined with optimization algorithm, we find the local maxima as well as the global maximum. A photonic crystal waveguide geometry is proposed which has a single-mode normalized bandwidth of 41% for TM polarization. This value is about 7% greater than the corresponding value for the commonly used square lattice of dielectric rods in which a row is removed. Also, some waveguide geometries are proposed for TE polarization and it is shown that one of these geometries can provide a single-mode bandwidth of 39%, while the widest bandwidth reported so far for the TE case is 21%. The dielectric material used for both cases is GaAs with a dielectric constant of 11.4.
Optica Applicata, Vol. 38, 2008, nr 4, s. 643-655
Keywords: optyka; photonic crystal waveguides; photonic bandgaps; optimization